Study on the Configuration Scheme Design and Parameter Matching of Heavy Duty Commercial Vehicles with Dual Electrical Drive Axles - Liu Benyou; Liu Junlong; Ji Jianyi; Han Shanling; Liu Minghao; Hu Jianlong; Han Zhendong (Jixie chuandong)
The electrification of heavy duty commercial vehicles is one of the critical path for solving its problems of high energy consumption and high pollutant emission. And the configuration scheme design and parameter matching of electric drive systems are the foundation of heavy duty commercial vehicle electrification. The dual driving axles of heavy duty trucks are taken as the research object. Then, the electric drive configuration scheme and parameter matching of the dual electric driving axles are studied. Several kinds of electrical drive configurations are analyzed and compared. Then, the dual electrical drive axles are determined. Specifically, the number of driving motors and the number of transmission gears are determined. Based on the configuration scheme, the main components structural performance parameters are calculated according to the functional and performance requirements of the vehicle. These parameters include power, speed and torque of the driving motors, the speed ratio of the transmission device, and the terminal voltage and capacity of the power battery. Then, the dynamic model of the electric heavy commercial vehicle is developed based on the designed configuration scheme and the matched components parameters. The dynamic and economy performance of this vehicle are simulated using the model. The simulation results show that the maximum speed can reach 100 km/h, the maximum grade-ability can reach 30%, and the driving range exceeds 300 km. It is illustrated that the configuration and parameters of the electric dual driving axles can meet the heavy commercial vehicle performance requirements. In the end, the relevant research can provide theoretical and technical support for the electrification of heavy commercial vehicles.